2019
DOI: 10.13057/biodiv/d210104
|View full text |Cite
|
Sign up to set email alerts
|

Activities and molecular characterization of petroleum hydrocarbons degrading rhizobacteria from mangrove plants (Rhizophora sp.) in Kulon Progo, Yogyakarta, Indonesia

Abstract: Abstract. Benget VV, Retnaningrum E. 2020. Activities and molecular characterization of petroleum hydrocarbons degrading rhizobacteria from mangrove plants (Rhizophora sp.) in Kulon Progo, Yogyakarta, Indonesia. Biodiversitas 21: 21-27. The increasing number of human population density around mangrove ecosystems has resulted in its pollution, particularly oil spills. Rhizobacteria have metabolic abilities that make them possible to live in polluted environmental conditions and the potential to be biological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several studies on biological agents for reducing oil pollution have been reported, including Staphylococcus pasteuri, Staphylococcus epidermidis, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus pumilus (Kanmani et al 2015;Lauprasert et al 2017;Saranya et al 2019). Other studies on the ability of the biological agents to degrade hydrocarbon pollutants have also been reported, including Pseudomonas aeruginosa, Pseudomonas sp, Bacillus sp (Retnaningrum and Wilopo 2017;Xia et al 2019;Sari and Retnaningrum 2019;Benget and Retnaningrum 2020). Bacterial isolates such as Pseudomonas sp, Rhodococcus sp, and Comamonas sp have been investigated for their potential in reducing plastics pollution (Urbanek et al 2018;Danso et al 2019), while Pseudomonas fluorescens can reduce pollutant pesticides (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on biological agents for reducing oil pollution have been reported, including Staphylococcus pasteuri, Staphylococcus epidermidis, Pseudomonas aeruginosa, Bacillus subtilis, Bacillus pumilus (Kanmani et al 2015;Lauprasert et al 2017;Saranya et al 2019). Other studies on the ability of the biological agents to degrade hydrocarbon pollutants have also been reported, including Pseudomonas aeruginosa, Pseudomonas sp, Bacillus sp (Retnaningrum and Wilopo 2017;Xia et al 2019;Sari and Retnaningrum 2019;Benget and Retnaningrum 2020). Bacterial isolates such as Pseudomonas sp, Rhodococcus sp, and Comamonas sp have been investigated for their potential in reducing plastics pollution (Urbanek et al 2018;Danso et al 2019), while Pseudomonas fluorescens can reduce pollutant pesticides (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%